The Leadership of Olly Dondokambey and the Diversity Condition of North Sulawesi - Rahman Mantu; Reiner Emyot Ointoe (Kawanua International Journal of Multicultural Studies, 2020)
The clash between religious-based groups, including problems with places of worship and deterrence of national Muslim leaders, has highly escalated in North Sulawesi.This is inversely proportional to the branding of North Sulawesi, especially Manado as a tolerant city. The public spotlight certainly leads to leadership at the regional level. Currently, the provincial government under the leadership of Olly Dondokambey, in terms of policy matters, is not very visible and has not been implemented, taking sides on diversity issues like what President Jokowi poured in Nawacita, which was revealed in many policies. In this article, the author notes that in many instances the government was less involved in the process of resolving clashes between groups. This article is written with a phenomenological approach, reveals cases, and analyzes them. The conclusion in this article is in the form of a recommendation to strengthen the regional vision and mission in favor of the issue of diversity.